Discovery and molecular characterisation of the first ambidensovirus in honey bees - Sabina OTT RUTAR; Dušan KORDIŠ (Acta Agriculturae Slovenica)
Honey bees play a critical role in global food production as pollinators of numerous crops. Several stressors cause declines in populations of managed and wild bee species, such as habitat degradation, pesticide exposure and pathogens. Viruses act as key stressors and can infect a wide range of species. The majority of honey bee-infecting viruses are RNA viruses of the Picornavirales order. Although some ssDNA viruses are common in insects, such as densoviruses, they have not yet been found in honey bees. Densoviruses were however found in bumblebees and ants. Here, we show that densoviruses are indeed present in the transcriptome of the eastern honey bee (Apis cerana) from southern China. On the basis of non-structural and structural transcripts, we inferred the genome structure of the Apis densovirus. Phylogenetic analysis has shown that this novel Apis densovirus belongs to the Scindoambidensovirus genus in the Densovirinae subfamily. Apis densovirus possesses ambisense genome organisation and encodes three non-structural proteins and a split VP (capsid) protein. The availability of a nearly complete Apis densovirus genome may enable the analysis of its potential pathogenic impact on honey bees. Our findings can thus guide further research into the densoviruses in honey bees and bumblebees.